Hayden Miller: capstone - Miller, Hayden, artist (Colorado State University. Libraries, 2018)
The artist's statement: My goal as a graphic designer is to meet the challenges and objectives I'm presented with by finding unique and innovative solutions. Regardless of the context I'm designing in, I strive to find the road less traveled in order to overcome challenges in an unexpected manner, which makes for a more involved experience for the viewer. I not only want to make the experience aesthetically pleasing for the viewer, but I also have the intent of making them contemplate how communication can be ambiguous by taking on many different forms. My work is inspired by my love for skateboarding and the subculture that surrounds it. Like the act of skateboarding, graphic design in the skateboard industry is very "in-your-face" and eye-catching, and it is this kind of attention grabbing communication that I try my best to achieve when working towards an objective. There is also a mindset ingrained in skateboarding that is constantly searching for the next new way to manipulate the skateboard, always looking to what's next and what's cool. I find myself thinking in a similar manner when working on a design project, because I want to discover new ways to utilize my skills and maximize my potential. My designs feature both precise geometric forms and spontaneous naturalistic mark making. I enjoy exploring industrialized environments as well as my beautiful home in Colorado for sources of visual inspiration, and I often bring in visual content to my projects from unexpected places.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design